"Connection to Culture Is Like a Massive Lifeline": Yarning With Aboriginal Young People About Culture and Social and Emotional Wellbeing. (August 2021) - Murrup-Stewart, Cammi; Whyman, Theoni; Jobson, Laura; Adams, Karen
Culture is an important social and emotional wellbeing factor for Aboriginal peoples in Australia, particularly regarding recovery from colonization. However, little is understood about how culture and wellbeing interact for young urban Aboriginal people. This study used Yarning methods to explore experiences and perceptions of culture and wellbeing for young urban Aboriginal people in Narrm, Australia. Findings indicate that culture is experienced as connection, and that perceived connection or disconnection has an essential influence on the wellbeing of young people. Through sharing young people stories, a range of factors, including colonization, relationships, cultural knowledge, community support, and agency, were identified as affecting perceptions of connectedness, and therefore on wellbeing. Youth were able to develop strategies to increase connection and provided illuminating advice and suggestions for improving connection for future generations. This study thus contributes to efforts to improved understanding of Aboriginal perspectives about social and emotional wellbeing and culture.